Innovation from below: dynamic capabilities of the territory as a source for new social ventures - Freitas Santos, José (2016)
Social innovation is a critical factor for the conception of new strategies to deal with increasingly complex social problems. Many of these initiatives are pursued at the local level and are based on the dynamic capabilities of a given territory. Through the analysis of the Cooperative Terra Chã, we assess whether dynamic capabilities of a territory can generate opportunities for social innovation and how they can be exploited by local communities. We observe that by using a integrated strategy for the management of the capabilities of a territory, new social ventures are able to cope with severe social issues that are not being adequately addressed by other stakeholders.